TINDAK PIDANA PENCURIAN PADA SAAT TERJADI BENCANA ALAM DALAM HUKUM PIDANA ISLAM DAN HUKUM POSITIF PERSPEKTIF MAQASID ASY-SYARI’AH - S, Sudarti (IAIN Tulungagung, 2020)
The victims of natural disasterswho commit theft cannot be immediately punished penalty in accordance with Islamic criminal law or positive law as contained in the Criminal Code. This study aims to analyze the problem of theft in the event of a natural disaster using the maqasid ash-sharia. This type of research is library research with descriptive analytical methods. The results showed that the daruriyyat aspect related to punishment for the perpetrators of theft was the aspect of maintaining property (ḥifż al-mal). This aspect is an aspect that is related to the obligation in the search for property lawfully without depriving others of their rights and managing property so that assets are maintained and functional in accordance with religious law.